Mercury and cadmium distribution in yellowfin tuna (Thunnus albacares) from two fishing grounds in the Indian Ocean near Sri Lanka - Jinadasa, B.K.K.K.; Chathurika, G.S.; Jayasinghe, G.D.T.M.; Jayaweera, C.D. (Elsevier Ltd., 2019)
Mercury (Hg) and cadmium (Cd) are contaminants of great environmental concern due to their natural and anthropogenic origin, their ability of bioaccumulate through the food chain and their harmful effects on human health. In this study, the Hg and Cd accumulation in the muscle of 65 yellowfin tuna (Thunnus albacares) collected from two different catching sites of the Indian Ocean near Sri Lanka were evaluated. The samples were mineralized using microwave accelerated digestion, and the metals were detected by atomic absorption spectroscopy (AAS). The metal levels were not significantly different between the two sites (p > 0.05), and the average Hg and Cd concentrations were 0.48 0.35 mg/kg and 0.017 0.024 mg/kg, (wet weight basis) respectively. Only 6 (9.2%) and 2 samples (3.1%) exceeded the European Commission limits for Hg (1 mg/kg) and Cd (0.01 mg/kg), respectively. A comparatively strong positive correlation was observed between the THg concentration and the weight of the fish. However, there was no clear relationship between the concentration and size for Cd. These findings provide an understanding of the Hg and Cd distribution in yellowfin tuna in two fishing grounds in the Indian Ocean near Sri Lanka.
Keywords: Toxicology Food science Food contamination Food safety Mercury Cadmium Yellowfin tuna Catching location